Microdata analysis of Japanese farmers' productivity: Estimating farm heterogeneity and elasticity of substitution among varieties. (24th May 2021) - Akune, Yuko; Hosoe, Nobuhiro
Abstract: Modern theories of trade and economic geography consider the role of product differentiation under monopolistic competition in manufacturing, under the assumption that agriculture produces homogeneous goods. By contrast, agribusiness studies examine the case of active high‐productivity entrepreneurs who pursue product differentiation by creating new products. To reconcile these two contradicting views of agriculture, we examine the incidence of farm heterogeneity and product differentiation. We use microdata of Japanese farmers to estimate their total factor productivity and find that heterogeneity is relatively low in the fruit, rice, and greenhouse horticulture farming sectors, and high in the livestock and poultry sectors. We find that the degree of product differentiation is relatively high in the livestock and poultry sectors, and that elasticity of substitution in the vegetable and upland field farming sectors is around three, which is similar to the findings of earlier studies.